[PP.03.07] PREDICTORS OF INCIDENT HYPERTENSION IN PREHYPERTENSIVES. (September 2016) - Ivkovic, V.; Parini, A.; Vrdoljak, A.; Karanovic, S.; Baric, M. Abramovic; Bachelli, S.; Cagnati, M.; Cicero, A.F.G.; D'Addato, S.; Esposti, D. degli; Fucek, M.; Grandi, E.; et al.
Abstract : Objective: Prehypertension (PHT) is associated ogeneous group but consists of susceptible subgroups some of which transition to HT. There is no consensus which factors predict progression which is of utmost pragmatic importance. Our aim was to examine IHT in PHT subjects and analyse predictive value of various risk factors. Design and method: In this analyzes we enrolleda subgroup of 279 PHT patients (m125, w154) from BrEna cohort which was formed from original cohorts of Brisighella Heart Study (Italy) and ENAH study (Croatia). They were followed-up for 84 months (IQ60–84) and a total of 1780 person-years of follow-up. PHT was defined as BP 120–139/80–89 mmHg. Exclusion criteria were antihypertensive medication, diabetes, pregnancy, eGFR<60 ml/min, cardiovascular or cerebrovascular incident, chronic terminal diseases, dementia, immobility and missing crucial data. BP was measured using Omron 6 device following the ESH guidelines. Fasting blood was analysed for glucose, lipids, uric acid, serum creatinine, leptin, adiponectin, hsCRP. HOMA index was used to calculate insulin resistance and Cocroft-Gault and MDRD formula to estimate GFR. Albumin to creatinine ratio (ACR) was determined from the first morning spot urine. Results: IHT was diagnosed in 134 PHT (48.2%, no between-gender difference) with incidence rate of 7.53% per year; 41.8% were treated and 26.8% controlled. At baseline, subjects who developed IHT vs. those who remained PHT at the end of follow-up differed in age (50 ± 12 vs. 39 ± 12), systolic BP (130 ± 13 vs. 125 ± 7), FBG (5.3 ± 0.7 vs. 4.9 ± 0.5), hsCRP (1.8 (IQ0.9–3.1) vs. 1.3 (IQ0.4–2.3), T-cholesterol (5.7 ± 1.1 vs. 5.4 ± 1.0), TG (1.3 (IQR 1.0–1.9) vs. 1.1 (IQR 0.8–1.6), ACR (5.0 (IQ3.6–6.9) vs. 4.2(IQ3.1–6.2), adiponectin (10.7 ± 4.1 vs. 16.5 ± 7.9), leptin (10.7 ± 6.0 vs. 8.1 ± 5.5), % of visceral obesity (47% vs. 31%), overweight (67% vs. 54%) and obesity (34% vs. 17%) all p < 0.05. Significant positive predictors of IHT were age, systolic BP and ACR. Conclusions: Incident rate of new-onset HT is high, and those subjects were poorly treated. Subgroup of PHT who developed IHT were older, had higher systolic BP, metabolic abnormalities and higher values of ACR. Lifestyle measures should be recommended to this subgroup early. Diagnostic and prognostic values of ACR for IHT in PHT should be further elaborated.